Implementasi Manajemen keuangan Sederhana bagi Siswa Teknik Mesin untuk Menumbuhkan Sikap Menghargai Rupiah Tanpa Judi Online Di SMK Persada Bhakti - Tutik Yuliani; Dika Karlinda Sari; Dwi Susilowati; Fransiskus Antonius Pabaru; Nur Raihaine Fetry (Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this Community Service activity is to provide students with an understanding of how to respect the rupiah without resorting to online gambling through the socialization activity